The moving researcher : Laban/Bartenieff Movement Analysis in performing arts education and creative arts therapies /: Laban/Bartenieff Movement Analysis in performing arts education and creative arts therapies. (2015) - Fernandes, Ciane, 1965-; Hand, Jackie
No abstract available